Profile of pregnant women in prison and their newborns. A case-control study (Research, Society and Development, 2025)
The increase in women in prison generates concern about the relationship with prison infrastructure and the guarantee of women's rights such as quality care for pregnant women and the exercise of motherhood. This study aims to analyze maternal and child health indicators of pregnant women and newborns inmates at the Tremembé Women's Penitentiary, SP, comparing them with those of the general population, and to evaluate the health outcomes of these groups, measuring risks and prognoses. It is a case-control study, composed of 106 pregnant inmates and their babies and 530 non-inmates randomly selected, from 2011 to 2022. The average variables of the inmates were: 25.6 years old; 2.2 pregnancies; 2 living children and 0.3 dead. The average start of prenatal care was 3.5 months with an average of 5.2 consultations. The mean variables of the newborns were: weight 3090.8 grams; Apgar scores at the first and fifth minute, respectively, of 7.9 and 8.9; gestational age of 38.4 weeks and most of the deliveries were vaginal. The pregnant women who were incarcerated were younger, had a greater number of previous pregnancies and live births, started prenatal care later, had fewer consultations, had a higher proportion of vaginal deliveries and were mostly without a partner, compared to the women who were not incarcerated. The level of education was similar between the groups. In this analysis it was possible to identify differences and similarities between the pregnant women in each group, but there were no statistical differences in the variables of the newborns.